Carbon disulfide-modified magnetic ion-imprinted chitosan-Fe(III): A novel adsorbent for simultaneous removal of tetracycline and cadmium. (2nd January 2017) - Chen, Anwei; Shang, Cui; Shao, Jihai; Lin, Yiqing; Luo, Si; Zhang, Jiachao; Huang, Hongli; Lei, Ming; Zeng, Qingru
Highlights: ⿢ MMIC-Fe(III) was developed for effective TC and Cd(II) removal simultaneously. ⿢ Ion-imprinted and surface modification technologies were coupled in the synthesis process. ⿢ Properties of MMIC-Fe(III) were greatly improved compared with those previously reported. ⿢ Synergistic effect of sorption were found due to the formation of complex TC-Cd(II) bridging. ⿢ The adsorption capacities are barely affected after five cycles. Abstract: A novel composite of carbon disulfide-modified magnetic ion-imprinted chitosan-Fe(III), i.e., MMIC-Fe(III) composite, was prepared as an efficient adsorbent for the simultaneous removal of tetracycline (TC) and Cd(II). This adsorbent showed excellent performance in removing TC and Cd(II) due to its rapid kinetics, high adsorption capacity, good reusability, and was well suited for use with real water samples. Kinetics studies demonstrated that the adsorption proceeded according to a pseudo-second order model. The adsorption isotherms were well described by the Langmuir model, with maximum adsorption capacity for TC and Cd(II) being 516.29 and 194.31 mg/g, respectively. The synergistic effect of TC and Cd(II) adsorption might be due to the formation of TC-Cd(II) complex bridging the adsorbate and adsorbent. These properties demonstrate the potential application of MMIC-Fe(III) for the simultaneous removal of TC and Cd(II), and may provide some information for the synergistic removal of antibiotics and heavy metals from aquatic environments.